Hydrolisis of palm olein to oleic acid using immobilized lipase in a recirculated packed bed batch reactor - Lee, C. T.; Yak, Y. L.; Razali, F.; Muhamad, Ida Idayu; Sarmidi, M. R. (Faculty of Chemical Engineering & Natural Resources, 2008)
Hydrolysis of palm olein to oleic acid using immobilized lipase from Asperigilfus niger with the trade name Lipozyme TL 1M was studied in a recirculated packed bed batch reactor (RPBBR). This study was conducted to investigate the kinetics of the enzymatic hydrolysis of palm olein and the potential of substrate inhibition using initial velocity analysis. The temperature and pH were set at 37Â°C and pH 7 while the stirrer speed was set at 250 rpm and the flow rate used was 0.5 mL. min". Hexane was selected as the solvent and gas chromatography was used to analyze the product samples. The range of substrate concentration being investigated ranged from 0.3 155 mol.L'! to 0.84 I2 mol. L-1. The kinetic model of Michaelis-Menten was used to analyze the kinetic data such as the maximum rate of reaction, Vmax and the Michaelis-Menten constant, Km. LineweaverBurk plot, Eadie-Hofstee plot and Hanes-Woolf plot were used to determine the Vmax and Km values and the average values of Vmax and Km obtained from these three plots were 0.00 I22 moLL-J.min" and 0.167 moLL,1 respectively. No substrate inhibition was observed for up to the palm olein concentration of 0.8412 mol .L".